2009
DOI: 10.1002/pc.20907
|View full text |Cite
|
Sign up to set email alerts
|

Vibration joining of fiber‐reinforced thermosets

Abstract: Adhesive bonding is known to be particularly suitable for thermoset composites with continuous fiber reinforcement as it does not interrupt the fibers because of drilled holes. The frequently used two-part adhesives often require long curing times for the chemical reaction. At the Institute of Polymer Technology (LKT), a vibration-assisted hot melt bonding technique (vibration joining) was developed, which offers short cycle times and represents a modification of hot melt bonding, using the machine technology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The friction-melted PA can fill these pockets (Figure 18) and increase mechanical interlocking, and thereby bond strength, between the EP and the PA. This study quantifies the effect of surface roughness on bonding, suggesting that 119 pretreating a surface would improve its adhesion and mechanical properties. Adhesion could perhaps be further enhanced if the materials are combined before the EP is fully cured, allowing for chemical bonding in addition to mechanical interlocking.…”
Section: Other Applications Of Polyamide-epoxy Interactionsmentioning
confidence: 99%
See 3 more Smart Citations
“…The friction-melted PA can fill these pockets (Figure 18) and increase mechanical interlocking, and thereby bond strength, between the EP and the PA. This study quantifies the effect of surface roughness on bonding, suggesting that 119 pretreating a surface would improve its adhesion and mechanical properties. Adhesion could perhaps be further enhanced if the materials are combined before the EP is fully cured, allowing for chemical bonding in addition to mechanical interlocking.…”
Section: Other Applications Of Polyamide-epoxy Interactionsmentioning
confidence: 99%
“…He co-cures PA films and EP/carbon fiber prepregs to form a network of intermingled polymer chains before friction welding components together by melting the PA regions together. Unlike Beiss, 119 the PA and EP are combined before the EP cures, allowing the potential for PA-EP covalent bonding in addition to the mechanical interlocking. Room temperature single lap shear strength was 75% greater in Hou’s composite than in Beiss’s, illustrating the importance of chemical as well as mechanical interlocking for adhesion.…”
Section: Other Applications Of Polyamide-epoxy Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2] Park et al [3] reported that due to the different natures of the two materials, joining composite components with metal alloys has been a serious problem. [4][5][6] Beiss et al [7] and Rhee et al [8] reported that the most common method of joining composite parts is adhesive bonding. Maressa et al [9] proposed that adhesive joints have a more even stress distribution, have lower stress concentration around corners, higher peel strength, and have a longer fatigue life than bolted joints.…”
Section: Introductionmentioning
confidence: 99%